Safety Cultures, Safety Models Taking Stock and Moving Forward (SpringerBriefs in Safety Management,, 2018)
The objective of this book is to help at-risk organizations to decipher the "safety cloud", and to position themselves in terms of operational decisions and improvement strategies in safety, considering the path already travelled, their context, objectives and constraints. What link can be established between safety culture and safety models in order to increase safety within companies carrying out dangerous activities? First, while the term "safety culture" is widely shared among the academic and industrial world, it leads to various interpretations and therefore different positioning when it comes to assess, improve or change it. Many safety theories, concepts, and models coexist today, being more or less appealing and/or directly useful to the industry. How, and based on which criteria, to choose from the available options? These are some of the questions addressed in this book, which benefits from the expertise of its worldwide famous authors in several industrial sectors. .